Adsorption-Desorption of Cd(II) and Mg(II) Ions by Dithizone-Immobilized Coal Bottom Ash - Dwi Putra Wijaya; Ridho Bonaventura; Nurharis Munandar; Fajar Hutagalung; Chairil Anwar (Indonesian Scholar Society, 2025)
Dithizone-immobilized coal bottom ash (DICBA) was successfully prepared as Cd(II) and Mg(II) adsorbent. The parameters examined in the metal ion adsorption study included the effect of pH, adsorbent mass, contact time, and initial concentration. Sequential desorption was examined using H2O, KNO3, HNO3, and Na2EDTA. The results showed that dithizone had been successfully immobilized on the activated coal bottom ash, as verified by FTIR spectroscopy and XRD analyses. Specific wavenumbers observed included the aromatic group C=C at 1496 cm-1, the C-N group at 1319 cm-1 and the Si-O-Si at 1087 cm-1 with d-spacing values of 8.313 and 6.046 Å. The optimum conditions for adsorption were 60 min for Cd(II) and 90 min for Mg(II) at a pH of 5 with 0.2 g of adsorbent mass, and an initial concentration of Cd(II) at 50 ppm. The adsorption kinetics of Cd(II) and Mg(II) followed the Ho pseudo-second-order model with 0.174 and 0.285 (g/mol·min) rate constants for Cd(II) and Mg(II), respectively. The highest correlation coefficients (R2) were 0.995 for Cd(II) and 0.999 for Mg(II). Isotherm modeling indicated that the adsorption of Cd(II) best fitted the Langmuir model (R² = 0.988), followed by the Dubinin–Radushkevich (R² = 0.952), Freundlich (R² = 0.843), and Temkin (R² = 0.827) models. The desorption mechanism for Cd(II) and Mg(II) was formed by various interactions, such as physical mechanism (28.25% and 26.26%), ion exchange (23.13% and 14.15%), hydrogen bond formation (16.90% and 12.11%), and the mechanism of complex formation (9.56% and 6.13%).